2009
DOI: 10.1021/jp900372d
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Ag+ and Au+ to Ethene

Abstract: For the reaction M(+)(C(2)H(4))(n-1) + C(2)H(4) --> M(+)(C(2)H(4))(n), where M = Ag, Au, the binding energies are predicted at the second order perturbation (MP2) and coupled cluster (CCSD(T)) levels of theory. As the basis set is systematically improved, the predicted M = Ag binding energies steadily improve, as compared to the experimental values. In fact, the complete basis set limit (CBS) predicted CCSD(T) binding energy for Ag(C(2)H(4))(+) is within experimental error. For MP2, as the basis set is improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…[27] The lack of back-donation may have an impact on the peculiar and powerful catalytic properties of Au I because, quite simply, it should tend to increase the electrophilicity of the coordinated substrate. [11] Most of the available theoretical work involving DCDtype analyses of alkene and alkyne complexes of Au I deals with bare Au-ethene + [25,[28][29][30][31][32] or Au-ethyne + [30] and generally tends to suggest that s donation largely dominates over p back-donation. Only when the presence of ancillary ligands (F À , bipyridines) was studied by natural bond order (NBO) analysis of orbital populations was a significantly larger or even dominating p back-donation found.…”
Section: Introductionmentioning
confidence: 99%
“…[27] The lack of back-donation may have an impact on the peculiar and powerful catalytic properties of Au I because, quite simply, it should tend to increase the electrophilicity of the coordinated substrate. [11] Most of the available theoretical work involving DCDtype analyses of alkene and alkyne complexes of Au I deals with bare Au-ethene + [25,[28][29][30][31][32] or Au-ethyne + [30] and generally tends to suggest that s donation largely dominates over p back-donation. Only when the presence of ancillary ligands (F À , bipyridines) was studied by natural bond order (NBO) analysis of orbital populations was a significantly larger or even dominating p back-donation found.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to compare binding energies of silver and gold cations with various unsaturated hydrocarbons in π-complexes. Complexes of basic alkenes and alkynes such as ethylene and acetylene were addressed previously. , We have already studied π-complexes of [Au­(PMe 3 )] + with unsaturated hydrocarbons . We have shown that both the type of the multiple bond and its substitution have a large effect on the binding energies.…”
Section: Resultsmentioning
confidence: 99%
“…1,9−13 The formation of such π-complexes is welldocumented by a number of experimental techniques ranging from infrared spectroscopy 9 and neutron scattering 11 to 1 H, 2 H, 13 C NMR, 10,13 electron spin resonance, 14 and molecular beam studies, 15 as well as computationally. 12,15 The formed πcomplexes account for the selectivity of ethylene adsorption on Ag + cations rather than on Brønsted acid sites in Ag/H-ZSM-5, which prevent its low-temperature oligomerization on this catalyst. 13 High stability of the π-complex prevents further involvement of ethylene in aromatization reaction on Ag/H-ZSM-5 at a temperature as high as 823 K. 13 Methane has been established to influence the reactivity of ethylene on Ag/H-ZSM-5 zeolite by decreasing the temperature of the π-complex involvement in chemical transformation by 150 K. In the presence of methane, ethylene π-complexes decompose and become involved in oligomerization and aromatization reaction at temperatures as low as 673 K. 13 This effect of methane on ethylene reactivity is rationalized by competitive interaction of methane with Ag + cationic sites.…”
Section: Introductionmentioning
confidence: 99%